2022
DOI: 10.1016/j.jiph.2021.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a novel SARS-CoV-2 Pango lineage B.1.1.526 in West Bengal, India

Abstract: Background Since its inception in late 2019, SARS-CoV-2 has been evolving continuously by procuring mutations, leading to emergence of numerous variants, causing second wave of pandemic in many countries including India in 2021. To control this pandemic continuous mutational surveillance and genomic epidemiology of circulating strains is very important to unveil the emergence of the novel variant and also monitor the evolution of existing variants. Methods SARS-CoV-2 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Therefore, in the present study, we have performed the whole‐genome mutational mapping and phylogenetic analysis of BA.1 and BA.2 lineages. We have downloaded 6 genome sequences each of BA.1 and BA.2, and also the genome sequence of the prototype strain (hCoV‐19/Wuhan/WIV04/2019) from the Global Initiative on Sharing All Influenza Data (GISAID) and performed whole‐genome mutational analysis according to the protocol described in Sarkar et al 5 , 6 Each of the six genomes of both BA.1 and BA.2 lineages was found to have 51 mutations dispersed throughout the genome, 32 of which are common to both lineages, whereas each lineage has 19 signature mutations. Among 32 common mutations, 21 are present in the S glycoprotein and the rest 11 are present in the other four coding regions (ORF1ab, E, M, and N).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the present study, we have performed the whole‐genome mutational mapping and phylogenetic analysis of BA.1 and BA.2 lineages. We have downloaded 6 genome sequences each of BA.1 and BA.2, and also the genome sequence of the prototype strain (hCoV‐19/Wuhan/WIV04/2019) from the Global Initiative on Sharing All Influenza Data (GISAID) and performed whole‐genome mutational analysis according to the protocol described in Sarkar et al 5 , 6 Each of the six genomes of both BA.1 and BA.2 lineages was found to have 51 mutations dispersed throughout the genome, 32 of which are common to both lineages, whereas each lineage has 19 signature mutations. Among 32 common mutations, 21 are present in the S glycoprotein and the rest 11 are present in the other four coding regions (ORF1ab, E, M, and N).…”
Section: Tablementioning
confidence: 99%
“…Nineteen unique mutations of BA.1 include 13 in the S glycoprotein and that of BA.2 includes 7 in the S glycoprotein (Table 1 ). Phylogenetic analysis of 12 genome sequences of Omicron variant, encompassing 6 genomes each of BA.1 and BA.2, along with the 2000 genomes of 25 different clades by Ultrafast Sample placement of Existing tRees, 6 , 7 revealed that genomes of Omicron variant formed a new cluster that emerged from the 20B clade (also known as GR) and also subdivided into two different subclusters (BA.1 and BA.2) based on the unique mutations (Figure 1 ).…”
Section: Tablementioning
confidence: 99%
“…Delta variant (B.1.617) was responsible for this deadly second wave of COVID-19 and was associated with breakthrough infections in the country ( 8 ). Previous studies have reported various circulating double-mutant (B.1.617) and triple-mutant strains (B.1.618) of SARS-CoV-2 across different regions of India, which are more pathogenic than the initial strains such as B.1.1.7 (Alpha), B.1.351 (Beta), and P.1 (Gamma) ( 9 ). After surviving the first and second waves of the SARS-CoV-2 virus, India was hit by a vicious third wave in January 2022.…”
Section: Introductionmentioning
confidence: 99%